Carboxylesterase-1 Assisted Targeting of HDAC Inhibitors to Mononuclear Myeloid Cells in Inflammatory Bowel Disease. (11th October 2021) - Elfiky, Ahmed M I; Ghiboub, Mohammed; Li Yim, Andrew Y F; Hageman, Ishtu L; Verhoeff, Jan; de Krijger, Manon; van Hamersveld, Patricia H P; Welting, Olaf; Admiraal, Iris; Rahman, Shafaque; Garcia-Vallejo, Juan J; Wildenberg, Manon E; et al.
Abstract: Background and Aims: Histone deacetylase inhibitors [HDACi] exert potent anti-inflammatory effects. Because of the ubiquitous expression of HDACs, clinical utility of HDACi is limited by off-target effects. Esterase-sensitive motif [ESM] technology aims to deliver ESM-conjugated compounds to human mononuclear myeloid cells, based on their expression of carboxylesterase 1 [CES1]. This study aims to investigate utility of an ESM-tagged HDACi in inflammatory bowel disease [IBD]. Methods: CES1 expression was assessed in human blood, in vitro differentiated macrophage and dendritic cells, and Crohn's disease [CD] colon mucosa, by mass cytometry, quantitative polymerase chain reaction [PCR], and immunofluorescence staining, respectively. ESM-HDAC528 intracellular retention was evaluated by mass spectrometry. Clinical efficacy of ESM-HDAC528 was tested in dextran sulphate sodium [DSS]-induced colitis and T cell transfer colitis models using transgenic mice expressing human CES1 under the CD68 promoter. Results: CES1 mRNA was highly expressed in human blood CD14 + monocytes, in vitro differentiated and lipopolysaccharide [LPS]-stimulated macrophages, and dendritic cells. Specific hydrolysis and intracellular retention of ESM-HDAC528 in CES1 + cells was demonstrated. ESM-HDAC528 inhibited LPS-stimulated IL-6 and TNF-α production 1000 times more potently than its control, HDAC800, in CES1 high monocytes. In healthy donor peripheral blood, CES1 expression was significantly higher in CD14 ++ CD16 - monocytes compared with CD14 + CD16 ++ monocytes. In CD-inflamed colon, a higher number of mucosal CD68 + macrophages expressed CES1 compared with non-inflamed mucosa. In vivo, ESM-HDAC528 reduced monocyte differentiation in the colon and significantly improved colitis in a T cell transfer model, while having limited potential in ameliorating DSS-induced colitis. Conclusions: We demonstrate that monocytes and inflammatory macrophages specifically express CES1, and can be preferentially targeted by ESM-HDAC528 to achieve therapeutic benefit in IBD.